ANA immunofluorescence versus profile-how well they perform in autoimmune diseases: an analysis of their clinical utility in a tertiary care centre - Petchiappan, Velammal; Guhan, Adityan; Selvam, Sumitra; Nagaprabu, V. N. (International Journal of Research in Medical Sciences, 2018)
Background: While Immunofluorescence assay remains the gold standard for the detection of ANA, Immunoprofile by ELISA is being increasingly utilized in view of easy availability and quick results. The study was done to find out whether ANA profile results are comparable with IFA. Methods: About 100 patients who had undergone both immunofluorescence and Immunoprofile were included. Immunofluorescence correlation with profile and their correlation with the disease were analyzed; sensitivity, specificity and predictive values were calculated. Results: ANA was positive in 78% by immunofluorescence; 73% by ANA profile. 22 patients in whom ANA IFA was negative were picked up by ANA profile. 27 patients who were not detected by ANA profile were tested positive by IFA. ANA testing by immuno profile had a sensitivity of 65% with a positive predictive value of 69% when compared with IFA. Immunofluorescence pattern and ANA profile correlated with the diagnosed disease in 63% and 49% respectively. Immunofluorescence pattern correlated with the ANA profile in only 35% of the study subjects. On correlation with the disease, ANA profile scored less compared to ANA-IFA with a sensitivity and specificity of 46% each; positive predictive value of 59%; negative predictive value of 33%. On analysis of individual disease, ANA profile is as good as IFA in SLE and scleroderma in terms of sensitivity. In Sjogren’s syndrome and MCTD, specificity and positive predictive value of ANA profile is high. Conclusions: ANA IFA performs better than immunoprofile in the diagnosis of autoimmune diseases.